HUBUNGAN TINGKAT KESEPIAN (LONELINESS) DENGAN PROBLEMATIC INTERNET USE (PIU) PADA MAHASISWA PENGGUNA INSTAGRAM - Sisilia Sipangkar; I Gusti Ngurah Juniartha; Ni Kadek Ayu Suarningsih (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
One of the developmental tasks of adolescence is to develop more mature relationships. Adolescents will be more comfortable with virtual interactions if they face challenges in their developmental tasks. Teens who are more comfortable with virtual interactions may experience loneliness. Many negative consequences will occur if teenagers are not aware of their obsessive behavior with social media. One of those is Problematic Internet Use (PIU). Individuals who have PIU are characterized by changes in their daily behavior patterns, which have an impact on their ability to organize their offline lives. The purpose of this study is to determine the relationship between the level of loneliness and PIU in students who use Instagram. This study is a descriptive correlative study with a cross-sectional approach. The sampling technique used was stratified random sampling, with a sample size of 138 students from the PSSIKPN, Faculty of Medicine, Udayana University during the 2018-2020 academic year. The UCLA Loneliness Scale 3 and GPIUS 2 questionnaires were used to collect data. The Spearman rank test yielded p value = 0.03 (p 0.05), indicating a very weak relationship between the level of loneliness and PIU in Instagram users, with a correlation coefficient value of 0.184. The higher the level of PIU for Instagram users at PSSIKPN, Faculty of Medicine, Udayana University, the higher the level of loneliness. It is hoped that as a result of these findings, students will be more cautious when using Instagram and will take the time to interact with those around them.